Intercultural stereotypes and the role of critical and creative thinking in overcoming them - Braslauskas, Justinas (Creativity Studies, 2023)
Intercultural stereotypes often lead to misunderstandings or even cultural conflicts in communication, as they interfere with the rational assessment of individuals from one national culture and the products, perspectives and practices associated with them. Although there is a considerable literature on stereotypes in general and on intercultural stereotypes in particular, there is clearly insufficient scholarly works to provide concrete and conceptual insights into how to minimise or overcome stereotypical attitudes in practice. For example, the role of critical and creative thinking in the process of devisualisation of stereotypes has not been adequately assessed in the academic literature. Researchers have so far paid little attention for it in their works. This work aims to fill the aforementioned gaps in the scientific discourse. The object of this article is intercultural stereotypes in the context of the link between critical and creative thinking. The aim of the article is to analyse the theoretical aspects of intercultural stereotypes and the role of critical and creative thinking in overcoming them. The work first analyses the theoretical aspects of stereotypes in the context of intercultural communication, and then examines the nuances of the role of critical and creative thinking in overcoming intercultural stereotypes. The role of critical and creative thinking in the process of overcoming intercultural stereotypes is explored by discussing the link between critical and creative thinking, as well as the importance of the application of teaching methods for critical and creative thinking skills in the process of devisualisation of stereotypes. The following research methods are used in order to implement the aim of the article: analysis and synthesis of scientific literature.